Testbuilder for TOEFL IBT : [Tests that Teach] - Vittorio, Pamela (Oxford Macmillan, 2011)
Designed to help improve students' exam performance and increase language competence, this title includes task types that familiarise students with the tasks they will face in the exam, practice and guidance pages that build confidence in answering them and an answer key that gives clear explanations as to why the given answer is incorrect
Keywords: Test of English as a Foreign Language -- English language -- English language--Examinations